The Influence of BIS Monitoring on Sedative Dose in Pediatric Patients Undergoing Open Muscle Biopsies – a Randomized Controlled Trial - Tschiedel, Eva; Müller, Oliver; Marina, Adela Della; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian (Klinische Pädiatrie, 2018)
Background The use of Propofol and Remifentanil for analgosedation in children is common and safe. For sedation monitoring clinical scores as Comfort Score (CS) as well as bispectral index (BIS) are frequently applied. The impact of BIS for sedation monitoring in pediatric patients is still under debate. This prospective study aims to investigate whether dual sedation monitoring of CS and BIS compared with monitoring of CS alone during muscle biopsies in children can reduce sedative doses, reduce awakening time and prevent complications.Methods 50 pediatric patients requiring sedation for open muscle biopsy were prospectively enrolled. Analgosedation was performed with remifentanil and propofol. Patients were randomly assigned to 2 groups: In 25 patients, sedation was monitored using CS alone, and in 25 patients CS and BIS monitoring were simultaneously applied. The primary outcome was the propofol dose applied during muscle biopsy. Secondary outcome parameters were recovery time and the frequency of complications.Results The median CS during the intervention in both groups was equal (11, P=1.000). The median BIS in group 2 was 59. No complications occurred in either group. There was no difference in propofol dose in either group (8.4 vs. 7.2 mg/kg/h; P=0.58) and no difference in the duration until eye opening (9 vs. 11 min; P=0.081).Conclusion For children undergoing minor surgical procedures under analgosedation, BIS monitoring does not affect the sedative dose, the time until eye opening or the frequency of complications.
Keywords: sedation monitoring; pediatric; bispectral index; comfort score; muscle biopsy